Interpretive policy analysis: Marshallese COFA migrants and the Affordable Care Act. Issue 1 (December 2016) - McElfish, Pearl; Purvis, Rachel; Maskarinec, Gregory; Bing, Williamina; Jacob, Christopher; Ritok-Lakien, Mandy; Rubon-Chutaro, Jellesen; Lang, Sharlynn; Mamis, Sammie; Riklon, Sheldon
Abstract Background Since the enactment of the Affordable Care Act (ACA), the rate of uninsured in the United States has declined significantly. However, not all legal residents have benefited equally. As part of a community-based participatory research (CBPR) partnership with the Marshallese community, an interpretative policy analysis research project was conducted to document Marshallese Compact of Free Association (COFA) migrants' understanding and experiences regarding the ACA and related health policies. This article is structured to allow the voice of Marshallese COFA migrants to explain their understanding and interpretation of the ACA and related polices on their health in their own words. Methods Qualitative data was collected from 48 participants in five focus groups conducted at the local community center and three individual interviews for those unable to attend the focus groups. Marshallese community co-investigators participated throughout the research and writing process to ensure that cultural context and nuances in meaning were accurately captured and presented. Community co-investigators assisted with the development of the semi-structured interview guide, facilitated focus groups, and participated in qualitative data analysis. Results Content analysis revealed six consistent themes across all focus groups and individual interviews that include: understanding, experiences, effect on health, relational/historical lenses, economic contribution, and pleas. Working with Marshallese community co-investigators, we selected quotations that most represented the participants' collective experiences. The Marshallese view the ACA and their lack of coverage as part of the broader relationship between the Republic of the Marshall Islands (RMI) and the United States. The Marshallese state that they have honored the COFA relationship, and they believe the United States is failing to meet its obligations of care and support outlined in the COFA. Conclusion While the ACA and Medicaid Expansion have reduced the national uninsured rate, Marshallese COFA migrants have not benefited equally from this policy. The lack of healthcare coverage for the Marshallese COFA migrants exacerbates the health disparities this underserved population faces. This article is an important contribution to researchers because it presents the Marshallese's interpretation of the policy, which will help inform policy makers that are working to improve Marshallese COFA migrant health.